Impact of cold atmospheric pressure argon plasma on antibiotic sensitivity of methicillin-resistant Staphylococcus aureus strains in vitro - Lührmann, Anne; Matthes, Rutger; Kramer, Axel (German Medical Science GMS Publishing House, 2016)
Aim: The antimicrobial activity of cold atmospheric pressure plasma (CAP), also called tissue tolerable plasma (TTP), could be a promising option to eradicate methicillin-sensitive as well as methicillin-resistant strains, which often colonize chronic wounds. Currently, the influence of CAP on the susceptibility of to antibiotics is scarcely known, but could be important for treatment of wounds. Therefore, the aim of this study was to investigate whether CAP has an impact on the susceptibility of different strains to different antibiotics.Method: For assessment, the agar diffusion test with different antibiotic test disks (cefuroxime, gentamicin, oxacillin, vancomycin, ciprofloxacin, co-trimoxazole, clindamycin, erythromycin) was used. Test strains were spread on agar plates and CAP treated before the antibiotic disks were placed. After 24 hours cultivation, the inhibited growth zones were measured and differences statistically evaluated.Results: In most cases, CAP had a negligible influence on the susceptibility to antibiotics. For two strains, the susceptibility significantly decreased to β-lactam antibiotics. Conclusion: Because CAP can influence the antibiotic susceptibility of , before conducting combined treatment with local plasma application on wounds and systemic antibiotics, their interaction must be analysed to exclude unwanted combination effects.